Nursing Care of 26 Infants Born to Mothers With COVID-19. (February 2022) - Ding, Lingli; Xiong, Xiaoju; Yu, Genzhen; Li, Changyan; Wang, Hui; Yang, Yiran; Wu, Shanshan; Cai, Xianglian
Abstract : Background: Novel coronavirus disease (COVID-19) has spread throughout the world; yet, there are few reports of neonatal cases. Thus, information about related clinical care experience is scarce. Clinical Findings: This case report includes 26 infants admitted to the neonatal intensive care unit (NICU) of Tongji Hospital in Wuhan City who were born to mothers with suspected/confirmed COVID-19. The nursing and medical staff implemented care of these infants in strict accordance with infection control measures. Intervention: Emergency measures for the prevention and control of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the NICU were developed, and neonatal isolation, observation, and treatment were performed. Outcomes: Vital signs of the 26 infants remained stable during isolation and treatment, and no complications occurred. During the study period, neither the infants nor the nursing and medical staff were infected with SARS-CoV-2. Practice Recommendations: Based on our strict practices, infants born to mothers with suspected/confirmed COVID-19 should receive care in a single-patient room to support infection control and provide enhanced observation. During initial contact and nursing care, increased attention should be given to the protection of infants born to mothers with suspected/confirmed COVID-19.